Immigration in the Covid-19 Era: The role of Greece and Turkey, the necessity for a common European immigration and foreign policy - Papadakis, Konstantinos; Zafeiris, Konstantinos (HAPSc Policy Briefs Series, 2020)
Immigration and refugee flows in the Eastern Mediterranean migration path have been increased the last two decades, a fact that created the need for coordinated political reaction from the EU, which now faces new challenges because of the Covid-19 pandemic. This article analyses the new challenges Covid-19 creates by focusing on the “lesson learned” of previous pandemics and their effect on mankind and also on the necessity of a common European policy both in the fields of immigration policy and foreign policy towards the stabilization in the Eastern Mediterranean, mainly by focusing on the role of Greece and Turkey.